A comparative study on competition law with regards to car manufacturing between Malaysia and United Kingdom / Nadiah Liyana Md Kudus …[et al.] - Md Kudus, Nadiah Liyana; Ahmad Yaakob, Nur Intanliana; Yusuff, Nurul Yusnafamieza; Roslan, Muhammad Azril; Turiman, Syahirah (2010)
Anti-competitive behaviour becomes a major problem in economy around the world. Prior to that, Malaysia has drafted its own competition law in which will be enforced in 2012. This law does not only govern anti-competitive conduct but also protects the consumers and small enterprises by protecting them from pressure given by the dominance. The main issue arises is whether Malaysian Competition Act 2010 (MCA 2010) is comprehensive to handle matters regarding anti-competitive behaviour, particularly in car manufacturing sector. In order to determine the effectiveness of MCA 2010, there is necessity to compare MCA 2010 with United Kingdom's Competition Act 1998 (UKCA 1998) as Malaysia has adopted some of UKCA 1998 fundamental principle into MCA 2010. By comparing both laws, we can see whether MCA 2010, the Act as a whole, is comprehensive enough to ensure and to promote competition between car manufacturers in Malaysian car manufacturing industry. This is because National Automotive Policy (NAP) was created in order to protect national car and thus, contradict with the objectives of the Act. Apart from that, Malaysian has agreed with ASEAN countries to have commitment with ASEAN Free Trade Area (AFTA) in liberalizing car market by lowering import duty which is also clearly contradict with NAP. If it is happened to be that the MCA 2010 is not comprehensive, car manufacturers in Malaysia will not have the opportunity to practice free competition between them. Therefore, it is important to ensure the effectiveness of MCA 2010 to ensure competition between car manufacturers despite the existence of NAP.